Proceedings of the 8th IEEE International NEWCAS Conference 2010 - Tannir, Dani (2010)
In this paper a moments based approach for computing the value of the third order intercept point and its sensitivity is presented. This approach eliminates the need to solve the Harmonic Balance equations and reduces the problem to that of solving a very sparse set of linear equations, thus significantly reducing the CPU cost of the simulation. Obtaining the sensitivity information efficiently provides a considerable advantage as it is critical for circuit optimization, design space exploration and design centering.